PENGARUH PENDEKATAN PEDAGOGI TERHADAP PEMAHAMAN SISWA DALAM PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 2 KOTABARU - Catur Darma Anita; Hayrun Anisa; Riona Reva Nisa; Siti Rahmatia; Salahuddin (Darul Ulum: Jurnal Ilmiah Keagamaan, Pendidikan dan Kemasyarakatan, 2026)
This research is motivated by the fact that the learning process of Islamic Religious Education (PAI) still tends to use conventional methods such as lectures and memorization, causing students to be less active and less able to understand the meaning of the material being taught. The pedagogical approach is an important factor that can influence learning success because it includes the teacher's ability to understand student characteristics, choose appropriate methods, and create a conducive learning atmosphere. The formulation of the research problems includes how teachers implement the pedagogical approach, how much influence it has on student understanding, and what factors support and hinder its implementation. The objectives of the study are to describe the implementation of the pedagogical approach, analyze the magnitude of its influence on student understanding, and identify supporting and inhibiting factors. This study employs a quantitative approach with a correlational and regression design. The research population consists of all students of SMP Negeri 2 Kotabaru, with a sample of 13 respondents selected using proportional random sampling technique. The research instruments include a questionnaire to measure students' perceptions of the teacher's pedagogical approach and a PAI comprehension test to measure students' level of understanding. Data collection techniques were carried out through observation, questionnaires, and documentation. Data analysis used descriptive and inferential statistics, including validity tests, reliability tests, normality tests, linearity tests, and simple linear regression analysis. The results show that the implementation of the pedagogical approach by PAI teachers is in the high category (76.9%–83.1%), with the highest indicator being the teacher's ability to relate PAI material to daily life (81.5%). There is a positive and significant influence of the pedagogical approach on student understanding with an R² value of 0.684, meaning that 68.4% of the variation in student understanding is explained by the pedagogical approach. The regression equation Y = 12.45 + 0.73X indicates that each one-point increase in the pedagogical approach will increase student understanding by 0.73 points. Supporting factors include teacher competence, student motivation, facilities and infrastructure, and school support, while inhibiting factors include time constraints, disparities in student abilities, low student participation, and lack of learning media. In conclusion, a varied and student-centered pedagogical approach is proven effective in improving PAI understanding at SMP Negeri 2 Kotabaru